Efficacy of viral load suppression on life expectancy of human immunodeficiency virus patients: a literature review - Bwambale Kyamakya, Moses; Niranjan, Vikram (International Journal of Community Medicine and Public Health, 2020)
In a bid mitigate the spread of HIV and AIDS since it was diagnosed, several interventions ranging from palliative care, increased access to HIV treatment to manage opportunistic infections and the current drive of improving clinical outcomes through suppression of viral load are all aimed at prolonging survival of HIV and AIDS patients. The authors endeavour to corroborate the effect of viral load (VL) suppression on ART HIV patients. The authors applied a comprehensive search by merging terms for survival of HIV patients to clinical, demographic and socio-economic factors in NCBI and MEDLINE databases. About 15 articles were considered by outlining research questions, generating key words and search terminologies. Only articles published since 2013 during scale up of VL interventions were considered. It is worth noting that unsuppressed VL clinically decisively causes death in HIV/AIDS patients, propelled by a number of associated causes including opportunistic infections (OIs) Tuberculosis (TB), Non communicable diseases (NCDs), age, sex, income, geographic location among others. Whereas there is marked decline in risk of dying among HIV/AIDS patients resulting from VL suppression, other factors including; early detection and timely treatment, managing OIs, NCDs and TB treatment, tackling socio-economic barriers and multi-pronged community focused interventions like Community Client Led ART Delivery CCLAD, Community Drug Distribution Point (CDDP) interventions enhance survival of HIV/AIDS patients on lifelong ART.
Keywords: Efficacy; HIV/AIDS; Life expectancy; Viral load